Respuesta :

For this case we have the following system of equations:

[tex]8x-5y = 11\\4x-3y = 5[/tex]

We multiply the second equation by -2:

[tex]-8x + 6y = -10[/tex]

Then we have the following equivalent system:

[tex]8x-5y = 11\\-8x + 6y = -10[/tex]

We add the equations:

[tex]8x-8x-5y + 6y = 11-10\\y = 1[/tex]

Thus, the value of the variable y is 1.

We look for the value of the variable x:

[tex]8x-5 (1) = 11\\8x-5 = 11\\8x = 11 + 5\\8x = 16\\x = \frac {16} {8}\\x = 2[/tex]

Thus, the value of the variable x is 2.

Then the point of intersection of the equations is in[tex](x, y) :( 2,1)[/tex]

Answer:

The point of intersection of the equations is in [tex](x, y) :( 2,1)[/tex]